2020
DOI: 10.3390/w12072035
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study at the Reservoir Head of Run-of-River Hydropower Plants in Gravel Bed Rivers. Part I: Delta Formation at Operation Level

Abstract: This study concerns scaled physical model tests of the delta formation process at the head of a run-of-river hydropower plant (RoR). It forms part of a larger research project to provide a scientific base for RoR sediment management strategies in medium-sized gravel bed rivers. The physical model consisted of an idealized river having a width of 20 m, a mean slope of 0.005, a mean flow rate of 22 m3/s and a 1-year flood flow of 104 m3/s. The model scale was 1:20. For the experiments, five different grain sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…This section summarizes the findings of delta formation experiments at the head of run-of-river hydropower plants as reported in Sindelar et al (2020). Human activities and climate changerelated effects have disturbed natural sediment dynamics in riverine systems on a global scale.…”
Section: Delta Formation At the Reservoir Of Head Of Run-of-river Hydropower Plants In Gravel Bed Riversmentioning
confidence: 99%
See 1 more Smart Citation
“…This section summarizes the findings of delta formation experiments at the head of run-of-river hydropower plants as reported in Sindelar et al (2020). Human activities and climate changerelated effects have disturbed natural sediment dynamics in riverine systems on a global scale.…”
Section: Delta Formation At the Reservoir Of Head Of Run-of-river Hydropower Plants In Gravel Bed Riversmentioning
confidence: 99%
“…The impounded section is termed "reservoir". The operation where the reservoir water level is lowered by opening the flood gate(s), such that a free surface flow develops is termed "flushing" (Sindelar et al, 2020).…”
Section: Delta Formation At the Reservoir Of Head Of Run-of-river Hydropower Plants In Gravel Bed Riversmentioning
confidence: 99%
“…The results of the flushing experiment by Reiterer et al (2020) showed the possibility of remobilizing delta depositions by (partial) drawdown flushing within a reasonable period (about 9 h in a 1:1 scale). The erosion of existing headwater delta deposition (compare to [2]) was found to be retrogressive and twice as fast as the preceding delta formation process. A spatiotemporal erosion scheme points out these findings.…”
mentioning
confidence: 90%
“…For the first category-to derive an advanced process understanding-the papers of The flood aspect, in terms of sediment management, was the central focus of Sindelar et al (2020). On the one hand, the study proved that the delta formation increases the flood risk at the head of the reservoir; on the other hand, the results showed that reservoir drawdowns at flood events of high probability were a promising strategy for enhancing sediment connectivity under the specified boundary conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation